PENERAPAN PELAYANAN HOLISTIK GEREJA DALAM KEBHINNEKAAN UMAT BERAGAMA DI INDONESIA - Eddy Danukusumah; Lusyana Yosepha Winata; Rikardo P. Sianipar (The Way: Jurnal Teologi dan Kependidikan, 2023)
This study aims to provide an understanding of the church's responsibility for holistic service in society, nation and state and to create a harmonious life so that the unity and integrity of Indonesia can be maintained. Republik Indonesia is the largest archipelagic country in the world with more than 17,000 islands. Through its uniqueness and diversity, Indonesia is known as a country with pluralistic society. This can be seen in the Indonesian value "Bhinneka Tunggal Ika", the word "bhinneka" means "different", an acknowledgment that the Indonesia is a nation with pluralism. Behavior that reflects the values ​​of unity and integrity in the social community is very much needed to maintain the nation. The Indonesian need to have solidarity based on the spirit of unity and unity in diversity in order to achieve a common goal, for the unity and welfare of Indonesia, for that the role of the church is very important in giving impact in the form of holistic services. The current study uses qualitative method, sourced from various literatures and journal articles related to the topic of discussion. The results of the study state that a church can carry out a holistic service function and have an impact on improving social welfare for a harmonious life in the unity and integrity Indonesia. The final conclusion states that the church should be able to have a real impact and function to play a holistic ministry such as koinonia, marturia, diakonia within the framework of Indonesian unity and integrity.